A DIGITAL WATERMARKING FOR RELATIONAL DATABASE: STATE OF ART TECHNIQUES - Islam Mohamed, Khalid El Drandaly, Walid Khedr, Ayman Mohamed Mostafa (International Journal of Advanced Science and Technology, 2020)
Recently the use of relational database system became increasing and that is why database watermarking is becoming one of the main techniques in securing relational databases. Relational database is widely used as a tool to store and manage data in many information systems; Digital watermarking is used to verify the authentication and integrity of data and ownership proofing. The proposed literature review presents a broad spectrum of relational database watermarking techniques and applications. The main goal of this paper is to highlight the state-of-the-art in watermarking techniques for relational databases to reflect recent research advances and to point out the key issues for future research. Different watermarking techniques and approaches utilized in relational database were highlighted along with their related issues and challenges. This paper surveyed a total of 2648 research papers published in the refereed conference and journals in the area of database watermarking and were surveyed in the interval from 2009 until 2019. From which 1286 primary studies were included and analyzed to constitute the source of present paper.